Entrepreneur-Region Fit and Entrepreneurial Success in China: The Effect of “Confucian” Personality - Zhou, Mingjie; Mu, Weiqi; Li, Fugui; Zhou, Yixin; Huang, Duan; Wang, Kexin; Zhang, Jianxin (Frontiers in Psychology, 2021)
Entrepreneur’s personality is associated with their entrepreneurial success, and regional personality plays a crucial role in the entrepreneurial ecosystem. Recently, scholars have called for an indigenous personality perspective and combining the entrepreneur’s personality with the regional personality. The current study innovates by investigating the indigenous Confucian personality (e.g., Interpersonal Relatedness, IR) and taking an entrepreneur-regional personality fit perspective, allowing to test how entrepreneurs interact with the local ecosystem. Using entrepreneurs’ personality data (N = 1386) from a representative sample across 44 major cities in China, we found that (1) city-level IR is curvilinearly correlated with entrepreneur’s annual income, with moderate IR associates with the highest income; and (2) the entrepreneur-regional fit analysis further revealed substantial interplay between entrepreneur and the city. Specifically, entrepreneurs who have moderate IR and run their business in the city also with moderate IR are most likely to have the highest income. Our study highlights the usefulness of investigating indigenous personality and the fit perspective in entrepreneurship research.